FIBRE SOURCING FOR THE NIGERIAN PULP MILLS: EVALUATION OF SUITABILITY INDICES OF SELECTED NIGERIAN RAINFOREST WOOD FIBRES - Nusirat A. Sadiku; Christiana M. Micheal (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2022)
To find a lasting solution to the problem of suitable fibre for pulp and papermaking in Nigeria, fibre suitability indices of nineteen wood species native to the rainforest zone of Nigeria were evaluated. Matured stems of the species were sourced and prepared for maceration. The fibre characteristics of the wood were carried out following ASTM D-1030-95 and ASTM D-1413-61. The fibres obtained were observed with the aid of a microscope and measurements of their morphology were done. A minimum of 25 fibres were measured for each species for accuracy. Selected morphological indices such as Runkel Ratio (RR), Flexibility Coefficient (FC), Slenderness Ratio (SR) as well as Rigidity Coefficient (RC) of the wood fibres were estimated. The results showed that the fibres lenght fall under short (1.05–1.36), medium-long (1.52–1.75), and long (2.0 mm) fibres criteria. All derived morphological indices showed significant variations from species to species. All fibres are not rigid and exhibited good SR with moderate rigidity and good felting power. They were all elastic; R. heudolotii and P. macrocarpa exhibited high elastic nature. They all have FC ≥ 50 and pass the RR ≤ 1, acceptable value for paper-making fibre except P. biglobosa and M. excelsa. The flexibility coefficients are in the range of 0.50 and 0.81. All the species pass the SR > 33 acceptable value for paper-making fibres. The species if harnessed as fibre blends in pulp and paper making furnish will help to solve the problem of inadequate long fibres for paper production in Nigerian pulp mills.